Marx, Romanticism and the Importance of Superstructure in Evaluating Progress. Issue 2 (3rd April 2017) - Johnson, Matthew
ABSTRACT: Marx's development and deployment of a teleological account of history derived, in part, from Hegelian tenets has been central to modern notions of progress. This stands in contrast to Rousseau's romanticism, which holds that human well-being declines as technology advances. In this article, I challenge these two positions through engagement with the case of Aboriginal Australian societies. I explore the possibility that an appreciation of the intricacies of societies demeaned as "primitive, " can lead Marxian and Rousseauian tenets to affirm those societies, but for reasons that Marx and Rousseau may not have originally appreciated. In light of the cultural or superstructural problems caused by modes of production, there may be grounds to appreciate the achievements of societies, which have actively rejected apparently essential means of progress, such as agriculture.